A wastewater deammoniation process based on ion exchange fiber
Through the ion-exchange fiber process, the combination of modified fibers and fillers is used to adsorb ammonia, which solves the problem of low efficiency in wastewater deaming process, achieves efficient ammonia removal and improves water quality.
Patent Information
- Application Number
- CN202410835366.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-26
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-06-26
AI Technical Summary
At this stage, the wastewater deaming process requires multiple cycles, which is inefficient and difficult to effectively treat high ammonia nitrogen wastewater, resulting in eutrophication of water bodies and water environment pollution.
Using a process based on ion exchange fibers, a strong acid-type ion exchange material is formed through the combination of modified fibers and modified fillers, and ammonia is adsorbed by cation exchange and pore structures to improve the ammonia removal efficiency.
It realizes efficient removal of ammonia in wastewater, reduces the number of cycles, improves the efficiency of ammonia removal, and significantly improves water quality.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wastewater deammoniation, and in particular to a wastewater deammoniation process based on ion exchange fibers. Background Art
[0002] Ammonia nitrogen exists in various types of wastewater such as industrial, agricultural and domestic wastewater. As a nutrient, excessive ammonia nitrogen will lead to eutrophication of water bodies, especially high ammonia nitrogen wastewater, which has a wide source and complex and changeable water quality, making it more harmful and more difficult to manage. At present, with the continuous development of fertilizer production, petroleum, aquaculture and other industries, the output of high ammonia nitrogen wastewater has gradually increased. Improper discharge of high ammonia nitrogen wastewater will cause eutrophication of water bodies and destroy the homeostasis of the water environment system, thereby causing severe hypoxia in the water body, which is not conducive to the growth of fish and aerobic aquatic organisms, and then cause the generation of black and smelly water bodies, endangering human physical and mental health. Therefore, it is urgent to study how to efficiently treat and recycle ammonia nitrogen in ammonia nitrogen wastewater, economically and effectively control the generation of high-concentration polluted wastewater from the source of discharge, and timely and effective treatment of high ammonia nitrogen wastewater has become an important research topic for current scientific researchers. Summary of the invention
[0003] The purpose of the present invention is to provide a wastewater deammoniation process based on ion exchange fibers, which solves the problem that the current wastewater deammoniation process requires multiple cycles.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A wastewater deammoniation process based on ion exchange fiber specifically comprises the following steps:
[0006] The wastewater is put into a liquid storage bottle, and a water pump, a liquid flow meter and the cavity side of the hollow fiber membrane contactor are connected to form a circulation loop. The shell side of the hollow fiber membrane contactor is connected with a valve, a vacuum gauge and a vacuum pump in sequence. The filter membrane in the hollow fiber membrane contactor is a modified filter membrane.
[0007] The modified filter membrane is prepared by the following steps:
[0008] Dissolve polyvinylidene fluoride in N,N-dimethylacetamide, add lithium chloride monohydrate, modified fiber and modified filler, stir for 6-8 hours at a rotation speed of 600-800r / min to obtain a casting solution, scrape the casting solution and soak it in deionized water for 2-3 days, take it out and dry it to obtain a modified filter membrane.
[0009] The weight ratio of the polyvinylidene fluoride, lithium chloride monohydrate, modified fiber and modified filler is 80-100:1-3:5-10:10-15.
[0010] Further, the modified fiber is prepared by the following steps:
[0011] Step A1: the bamboo fiber and the sodium hydroxide solution are mixed evenly, stirred for 30-40 minutes at a speed of 200-300 r / min and a temperature of 25-30° C., and then washed with deionized water until neutral to obtain activated fiber; the activated fiber, lithium chloride, maleic anhydride, 4-dimethylaminopyridine and N,N-dimethylacetamide are mixed evenly, reacted for 6-8 hours at a speed of 120-150 r / min and a temperature of 60-70° C. to obtain pretreated fiber;
[0012] Step A2: The pretreated fiber, glycidyl methacrylate, benzoyl peroxide, deionized water and N,N-dimethylformamide are mixed evenly, and the mixture is reacted for 2-3 hours at a speed of 60-80 r / min and a temperature of 80-85° C., and the mixture is heated to 90-95° C. and reacted for 2-3 hours. Sodium aminosulfonate is added to a pH value of 8-10, and the mixture is reacted for 15-20 hours to obtain the modified fiber.
[0013] Furthermore, the mass ratio of the bamboo fiber and the sodium hydroxide solution described in step A1 is 1:20, the mass fraction of the sodium hydroxide solution is 15%, the mass ratio of the activated fiber, lithium chloride and maleic anhydride is 1:1:2, and the amount of 4-dimethylaminopyridine used is 0.1% of the mass of maleic anhydride.
[0014] Furthermore, the amount ratio of the pretreated fiber, glycidyl methacrylate and sodium aminosulfonate described in step A2 is 1g:3mL:0.5g, and the amount of benzoyl peroxide is 0.2% of the mass of glycidyl methacrylate.
[0015] Further, the modified filler is prepared by the following steps:
[0016] Step B1: zeolite, calcium chloride hexahydrate and deionized water are mixed, stirred for 1-1.5 hours at a speed of 600-800 r / min and a temperature of 20-25°C, and then vacuum dried. The substrate is dispersed in ethanol, stirred and KH550 and deionized water are added at a speed of 120-150 r / min and a temperature of 40-50°C, and reacted for 3-5 hours to obtain a modified zeolite. 2-aminoterephthalic acid, zinc nitrate hexahydrate and N,N-dimethylformamide are mixed evenly, and reacted for 20-25 hours at a speed of 120-150 r / min and a temperature of 110-115°C to obtain a functionalized zinc organic framework;
[0017] Step B2: Ethylene glycol, epichlorohydrin, tetrabutylammonium bromide and N,N-dimethylformamide are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out for 2-3 hours at a speed of 120-150r / min and a temperature of 110-115°C, and the temperature is lowered to 50-55°C, and sodium hydroxide solution is added to react for 5-7 hours to obtain a modifier, and the modified zeolite, functionalized zinc organic framework and N,N-dimethylformamide are mixed evenly, and the modifier is added at a speed of 150-200r / min, a temperature of 60-70°C, and a pH value of 10-11, and the reaction is carried out for 6-8 hours to obtain a composite matrix;
[0018] Step B3: Disperse the composite matrix in tetrahydrofuran, stir and add acryloyl chloride and p-toluenesulfonamide at a speed of 60-80r / min and a temperature of 40-50°C, and react for 3-5h to obtain a modified matrix; mix the modified matrix, acrylamide, methacryloyloxyethyltrimethylammonium chloride and deionized water evenly, introduce nitrogen protection, stir and add ammonium persulfate at a speed of 60-80r / min and a temperature of 80-85°C, and react for 4-6h to obtain a modified filler.
[0019] Furthermore, the dosage ratio of the zeolite, calcium chloride hexahydrate and deionized water in step B1 is 1 g:8 g:20 mL, the dosage of KH550 is 1.5% of the mass of the zeolite, and the molar ratio of 2-aminoterephthalic acid and zinc nitrate hexahydrate is 1:4.
[0020] Furthermore, the dosage ratio of ethylene glycol, epichlorohydrin, tetrabutylammonium bromide and sodium hydroxide solution in step B2 is 100 mmol: 200 mmol: 0.5 g: 30 mL, the mass fraction of the sodium hydroxide solution is 50%, and the molar ratio of the amino group on the modified zeolite, the amino group on the functionalized zinc organic framework and the modifier is 1: 1: 1.1.
[0021] Furthermore, the usage ratio of the composite matrix and acryloyl chloride described in step B3 is 1g:1.5mL, the usage of p-toluenesulfonamide is 0.2% of the mass of acryloyl chloride, the usage of the modified matrix, acrylamide, and methacryloyloxyethyltrimethylammonium chloride is 1g:40mmol:40mmol, and the usage of ammonium persulfate is 0.5% of the mass of acrylamide.
[0022] Beneficial effects of the invention: The invention discloses a wastewater deammoniation process based on ion exchange fiber, wherein wastewater is put into a liquid storage bottle, a water pump, a liquid flow meter and the cavity side of a hollow fiber membrane contactor are connected to form a circulation loop, a valve, a vacuum gauge and a vacuum pump are sequentially connected to the shell side of the hollow fiber membrane contactor, the filter membrane in the hollow fiber membrane contactor is a modified filter membrane, and the modified filter membrane comprises the following raw materials: polyvinylidene fluoride, lithium chloride monohydrate, modified fiber and modified filler, the modified fiber is treated with a sodium hydroxide solution using bamboo fiber as a raw material to obtain an activated fiber, the activated fiber is treated with maleic anhydride to open the maleic anhydride ring and esterify with a hydroxyl group to obtain The pretreated fiber is prepared, and the pretreated fiber is mixed with glycidyl methacrylate under the action of benzoyl peroxide to polymerize the double bonds on the pretreated cellulose and the double bonds on the glycidyl methacrylate. Then, under the action of sodium sulfamate, the epoxy group and the sodium sulfamate react to form a strong acid ion exchange fiber to prepare a modified fiber. The modified filler is made of zeolite and calcium chloride hexahydrate as raw materials, which are mixed in water, and calcium chloride is loaded in the pores of the zeolite. Then, the surface is treated with KH550 to graft active amino groups on the surface to prepare a modified zeolite. 2-aminoterephthalic acid and zinc nitrate hexahydrate are combined to form a functional zeolite containing active amino groups. The invention relates to a functionalized zinc organic framework, wherein ethylene glycol and epichlorohydrin are reacted so that the alcohol hydroxyl group on the ethylene glycol reacts with the epoxy group on the epichlorohydrin, and then the ring is closed under the action of a sodium hydroxide solution to form an epoxy group, thereby obtaining a modifier, wherein the modified zeolite and the functionalized zinc organic framework are treated with the modifier so that the epoxy group on the modifier reacts with the amino group on the modified zeolite and the amino group on the functionalized zinc organic framework to form a new hydroxyl group, thereby obtaining a composite body, wherein the composite body is reacted with acryloyl chloride so that the hydroxyl group on the composite body reacts with the acyl chloride on the acryloyl chloride to obtain a modified matrix, and wherein the modified matrix, acrylamide and methacryloyloxyethyl trimethyl Ammonium chloride is polymerized to obtain a modified filler. When wastewater contacts the modified filter membrane, the cations on the modified fiber and the modified filler can exchange ions with the ammonia in the wastewater and adsorb the ammonia in the pores of the modified fiber and the modified filler. The zinc-organic framework on the surface of the modified filler can provide a large number of gaps and has more acidic sites to increase the capture amount of ammonia. The zeolite structure is contained inside, and the zeolite contains calcium chloride. The electronegativity of the zeolite surface can further absorb the ammonia stored in the zinc-organic framework, allowing the ammonia to contact with the calcium chloride, and then emptying the ammonia in the zinc-organic framework, increasing the storage space for ammonia and improving the removal efficiency of ammonia in wastewater. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example
[0024] A wastewater deammoniation process based on ion exchange fiber specifically comprises the following steps:
[0025] The wastewater is put into a liquid storage bottle, and a water pump, a liquid flow meter and the cavity side of the hollow fiber membrane contactor are connected to form a circulation loop. The shell side of the hollow fiber membrane contactor is connected with a valve, a vacuum gauge and a vacuum pump in sequence. The filter membrane in the hollow fiber membrane contactor is a modified filter membrane, and the flow rate of the wastewater is 7L / h.
[0026] The modified filter membrane is prepared by the following steps:
[0027] Dissolve polyvinylidene fluoride in N,N-dimethylacetamide, add lithium chloride monohydrate, modified fiber and modified filler, stir for 6 hours at a rotation speed of 600r / min to obtain a casting solution, scrape the casting solution and soak it in deionized water for 2 days, take it out and dry it to obtain a modified filter membrane.
[0028] The weight ratio of the polyvinylidene fluoride, lithium chloride monohydrate, modified fiber and modified filler is 80:1:5:10, and the model of the polyvinylidene fluoride is W#2100.
[0029] The modified fiber is prepared by the following steps:
[0030] Step A1: The bamboo fiber and the sodium hydroxide solution are mixed evenly, stirred for 30 minutes at a speed of 200 r / min and a temperature of 25° C., and then washed with deionized water until neutral to obtain activated fiber; the activated fiber, lithium chloride, maleic anhydride, 4-dimethylaminopyridine and N,N-dimethylacetamide are mixed evenly, and reacted for 6 hours at a speed of 120 r / min and a temperature of 60° C. to obtain pretreated fiber;
[0031] Step A2: The pretreated fiber, glycidyl methacrylate, benzoyl peroxide, deionized water and N,N-dimethylformamide were mixed evenly, and the reaction was carried out at a speed of 60 r / min and a temperature of 80°C for 2 hours, and the temperature was raised to 90°C and the reaction was carried out for 2 hours. Sodium aminosulfonate was added to a pH value of 8, and the reaction was carried out for 15 hours to obtain modified fiber.
[0032] The mass ratio of the bamboo fiber and the sodium hydroxide solution described in step A1 is 1:20, the mass fraction of the sodium hydroxide solution is 15%, the mass ratio of the activated fiber, lithium chloride and maleic anhydride is 1:1:2, and the amount of 4-dimethylaminopyridine used is 0.1% of the mass of maleic anhydride.
[0033] The amount ratio of the pretreated fiber, glycidyl methacrylate and sodium aminosulfonate described in step A2 is 1g:3mL:0.5g, and the amount of benzoyl peroxide is 0.2% of the mass of glycidyl methacrylate.
[0034] The modified filler is prepared by the following steps:
[0035] Step B1: zeolite, calcium chloride hexahydrate and deionized water are mixed, stirred for 1 hour at a speed of 600 r / min and a temperature of 20°C, and then vacuum dried. The substrate is dispersed in ethanol, stirred and KH550 and deionized water are added at a speed of 120 r / min and a temperature of 40°C, and reacted for 3 hours to obtain a modified zeolite. 2-aminoterephthalic acid, zinc nitrate hexahydrate and N,N-dimethylformamide are mixed evenly, and reacted for 20 hours at a speed of 120 r / min and a temperature of 110°C to obtain a functionalized zinc organic framework;
[0036] Step B2: Ethylene glycol, epichlorohydrin, tetrabutylammonium bromide and N,N-dimethylformamide are mixed evenly, nitrogen is introduced for protection, and the mixture is reacted for 2 hours at a speed of 120 r / min and a temperature of 110°C, then cooled to 50°C, a sodium hydroxide solution is added, and the mixture is reacted for 5 hours to obtain a modifier, and the modified zeolite, functionalized zinc organic framework and N,N-dimethylformamide are mixed evenly, and the mixture is stirred and the modifier is added at a speed of 150 r / min, a temperature of 60°C and a pH value of 10, and the mixture is reacted for 6 hours to obtain a composite matrix;
[0037] Step B3: Disperse the composite matrix in tetrahydrofuran, stir and add acryloyl chloride and p-toluenesulfonamide at a speed of 60 r / min and a temperature of 40°C, and react for 3 hours to obtain a modified matrix; mix the modified matrix, acrylamide, methacryloyloxyethyltrimethylammonium chloride and deionized water evenly, introduce nitrogen protection, stir and add ammonium persulfate at a speed of 60 r / min and a temperature of 80°C, and react for 4 hours to obtain a modified filler.
[0038] The dosage ratio of the zeolite, calcium chloride hexahydrate and deionized water in step B1 is 1 g:8 g:20 mL, the dosage of KH550 is 1.5% of the mass of the zeolite, and the molar ratio of 2-aminoterephthalic acid and zinc nitrate hexahydrate is 1:4.
[0039] The amount ratio of ethylene glycol, epichlorohydrin, tetrabutylammonium bromide and sodium hydroxide solution in step B2 is 100mmol:200mmol:0.5g:30mL, the mass fraction of sodium hydroxide solution is 50%, and the molar ratio of amino groups on the modified zeolite, amino groups on the functionalized zinc organic framework and the modifier is 1:1:1.1.
[0040] The usage ratio of the composite matrix and acryloyl chloride described in step B3 is 1g:1.5mL, the usage of p-toluenesulfonamide is 0.2% of the mass of acryloyl chloride, the usage of the modified matrix, acrylamide, and methacryloyloxyethyltrimethylammonium chloride is 1g:40mmol:40mmol, and the usage of ammonium persulfate is 0.5% of the mass of acrylamide. Example
[0041] A wastewater deammoniation process based on ion exchange fiber specifically comprises the following steps:
[0042] The wastewater is put into a liquid storage bottle, and a water pump, a liquid flow meter and the cavity side of the hollow fiber membrane contactor are connected to form a circulation loop. The shell side of the hollow fiber membrane contactor is connected with a valve, a vacuum gauge and a vacuum pump in sequence. The filter membrane in the hollow fiber membrane contactor is a modified filter membrane, and the flow rate of the wastewater is 7L / h.
[0043] The modified filter membrane is prepared by the following steps:
[0044] Dissolve polyvinylidene fluoride in N,N-dimethylacetamide, add lithium chloride monohydrate, modified fiber and modified filler, stir for 7 hours at a rotation speed of 600r / min to obtain a casting solution, scrape the casting solution and soak it in deionized water for 2 days, take it out and dry it to obtain a modified filter membrane.
[0045] The weight ratio of the polyvinylidene fluoride, lithium chloride monohydrate, modified fiber and modified filler is 90:2:8:13, and the model of the polyvinylidene fluoride is W#2100.
[0046] The modified fiber is prepared by the following steps:
[0047] Step A1: The bamboo fiber and the sodium hydroxide solution are mixed evenly, stirred for 35 minutes at a speed of 200 r / min and a temperature of 28° C., and then washed with deionized water until neutral to obtain activated fiber; the activated fiber, lithium chloride, maleic anhydride, 4-dimethylaminopyridine and N,N-dimethylacetamide are mixed evenly, reacted for 7 hours at a speed of 120 r / min and a temperature of 65° C. to obtain pretreated fiber;
[0048] Step A2: The pretreated fiber, glycidyl methacrylate, benzoyl peroxide, deionized water and N,N-dimethylformamide were mixed evenly, and the reaction was carried out at a speed of 60 r / min and a temperature of 83° C. for 2 h, and the temperature was raised to 93° C. and the reaction was carried out for 2.5 h. Sodium aminosulfonate was added to a pH value of 9 and the reaction was carried out for 18 h to obtain modified fiber.
[0049] The mass ratio of the bamboo fiber and the sodium hydroxide solution described in step A1 is 1:20, the mass fraction of the sodium hydroxide solution is 15%, the mass ratio of the activated fiber, lithium chloride and maleic anhydride is 1:1:2, and the amount of 4-dimethylaminopyridine used is 0.1% of the mass of maleic anhydride.
[0050] The amount ratio of the pretreated fiber, glycidyl methacrylate and sodium aminosulfonate described in step A2 is 1g:3mL:0.5g, and the amount of benzoyl peroxide is 0.2% of the mass of glycidyl methacrylate.
[0051] The modified filler is prepared by the following steps:
[0052] Step B1: zeolite, calcium chloride hexahydrate and deionized water are mixed, stirred for 1.5 hours at a speed of 600 r / min and a temperature of 23°C, and then vacuum dried. The substrate is dispersed in ethanol, stirred and KH550 and deionized water are added at a speed of 120 r / min and a temperature of 45°C, and reacted for 4 hours to obtain a modified zeolite. 2-aminoterephthalic acid, zinc nitrate hexahydrate and N,N-dimethylformamide are mixed evenly, and reacted for 23 hours at a speed of 120 r / min and a temperature of 113°C to obtain a functionalized zinc organic framework;
[0053] Step B2: Ethylene glycol, epichlorohydrin, tetrabutylammonium bromide and N,N-dimethylformamide were mixed evenly, nitrogen was introduced for protection, the reaction was carried out for 3 hours at a speed of 120 r / min and a temperature of 113°C, the temperature was lowered to 53°C, sodium hydroxide solution was added, and the reaction was carried out for 6 hours to obtain a modifier, and the modified zeolite, functionalized zinc organic framework and N,N-dimethylformamide were mixed evenly, the speed was 150 r / min, the temperature was 65°C, and the pH value was 10, the modifier was added, and the reaction was carried out for 7 hours to obtain a composite matrix;
[0054] Step B3: Disperse the composite matrix in tetrahydrofuran, stir and add acryloyl chloride and p-toluenesulfonamide at a speed of 60 r / min and a temperature of 45°C, and react for 4 hours to obtain a modified matrix; mix the modified matrix, acrylamide, methacryloyloxyethyltrimethylammonium chloride and deionized water evenly, introduce nitrogen protection, stir and add ammonium persulfate at a speed of 60 r / min and a temperature of 83°C, and react for 5 hours to obtain a modified filler.
[0055] The dosage ratio of the zeolite, calcium chloride hexahydrate and deionized water in step B1 is 1 g:8 g:20 mL, the dosage of KH550 is 1.5% of the mass of the zeolite, and the molar ratio of 2-aminoterephthalic acid and zinc nitrate hexahydrate is 1:4.
[0056] The amount ratio of ethylene glycol, epichlorohydrin, tetrabutylammonium bromide and sodium hydroxide solution in step B2 is 100mmol:200mmol:0.5g:30mL, the mass fraction of sodium hydroxide solution is 50%, and the molar ratio of amino groups on the modified zeolite, amino groups on the functionalized zinc organic framework and the modifier is 1:1:1.1.
[0057] The usage ratio of the composite matrix and acryloyl chloride described in step B3 is 1g:1.5mL, the usage of p-toluenesulfonamide is 0.2% of the mass of acryloyl chloride, the usage of the modified matrix, acrylamide, and methacryloyloxyethyltrimethylammonium chloride is 1g:40mmol:40mmol, and the usage of ammonium persulfate is 0.5% of the mass of acrylamide. Example
[0058] A wastewater deammoniation process based on ion exchange fiber specifically comprises the following steps:
[0059] The wastewater is put into a liquid storage bottle, and a water pump, a liquid flow meter and the cavity side of the hollow fiber membrane contactor are connected to form a circulation loop. The shell side of the hollow fiber membrane contactor is connected with a valve, a vacuum gauge and a vacuum pump in sequence. The filter membrane in the hollow fiber membrane contactor is a modified filter membrane, and the flow rate of the wastewater is 7L / h.
[0060] The modified filter membrane is prepared by the following steps:
[0061] Dissolve polyvinylidene fluoride in N,N-dimethylacetamide, add lithium chloride monohydrate, modified fiber and modified filler, stir for 8 hours at a rotation speed of 800r / min to obtain a casting solution, scrape the casting solution and soak it in deionized water for 3 days, take it out and dry it to obtain a modified filter membrane.
[0062] The weight ratio of the polyvinylidene fluoride, lithium chloride monohydrate, modified fiber and modified filler is 100:3:10:15, and the model of the polyvinylidene fluoride is W#2100.
[0063] The modified fiber is prepared by the following steps:
[0064] Step A1: The bamboo fiber and the sodium hydroxide solution are mixed evenly, stirred for 40 minutes at a speed of 300 r / min and a temperature of 30° C., and then washed with deionized water until neutral to obtain activated fiber; the activated fiber, lithium chloride, maleic anhydride, 4-dimethylaminopyridine and N,N-dimethylacetamide are mixed evenly, reacted for 8 hours at a speed of 150 r / min and a temperature of 70° C. to obtain pretreated fiber;
[0065] Step A2: The pretreated fiber, glycidyl methacrylate, benzoyl peroxide, deionized water and N,N-dimethylformamide were mixed evenly, and the reaction was carried out for 3 hours at a speed of 80 r / min and a temperature of 85°C. The temperature was raised to 95°C and the reaction was carried out for 3 hours. Sodium aminosulfonate was added to a pH value of 10 and the reaction was carried out for 20 hours to obtain modified fiber.
[0066] The mass ratio of the bamboo fiber and the sodium hydroxide solution described in step A1 is 1:20, the mass fraction of the sodium hydroxide solution is 15%, the mass ratio of the activated fiber, lithium chloride and maleic anhydride is 1:1:2, and the amount of 4-dimethylaminopyridine used is 0.1% of the mass of maleic anhydride.
[0067] The amount ratio of the pretreated fiber, glycidyl methacrylate and sodium aminosulfonate described in step A2 is 1g:3mL:0.5g, and the amount of benzoyl peroxide is 0.2% of the mass of glycidyl methacrylate.
[0068] The modified filler is prepared by the following steps:
[0069] Step B1: zeolite, calcium chloride hexahydrate and deionized water are mixed, stirred for 1.5 hours at a speed of 800 r / min and a temperature of 25°C, and then vacuum dried. The substrate is dispersed in ethanol, stirred and KH550 and deionized water are added at a speed of 150 r / min and a temperature of 50°C, and reacted for 5 hours to obtain a modified zeolite. 2-aminoterephthalic acid, zinc nitrate hexahydrate and N,N-dimethylformamide are mixed evenly, and reacted for 25 hours at a speed of 150 r / min and a temperature of 115°C to obtain a functionalized zinc organic framework;
[0070] Step B2: Ethylene glycol, epichlorohydrin, tetrabutylammonium bromide and N,N-dimethylformamide were mixed evenly, nitrogen was introduced for protection, the reaction was carried out for 3 hours at a speed of 150 r / min and a temperature of 115°C, the temperature was lowered to 55°C, sodium hydroxide solution was added, and the reaction was carried out for 7 hours to obtain a modifier, and the modified zeolite, functionalized zinc organic framework and N,N-dimethylformamide were mixed evenly, the speed was 200 r / min, the temperature was 70°C, and the pH value was 11, the modifier was added, and the reaction was carried out for 8 hours to obtain a composite matrix;
[0071] Step B3: Disperse the composite matrix in tetrahydrofuran, stir and add acryloyl chloride and p-toluenesulfonamide at a speed of 80 r / min and a temperature of 50°C, and react for 5 hours to obtain a modified matrix; mix the modified matrix, acrylamide, methacryloyloxyethyltrimethylammonium chloride and deionized water evenly, introduce nitrogen protection, stir and add ammonium persulfate at a speed of 80 r / min and a temperature of 85°C, and react for 6 hours to obtain a modified filler.
[0072] The dosage ratio of the zeolite, calcium chloride hexahydrate and deionized water in step B1 is 1 g:8 g:20 mL, the dosage of KH550 is 1.5% of the mass of the zeolite, and the molar ratio of 2-aminoterephthalic acid and zinc nitrate hexahydrate is 1:4.
[0073] The amount ratio of ethylene glycol, epichlorohydrin, tetrabutylammonium bromide and sodium hydroxide solution in step B2 is 100mmol:200mmol:0.5g:30mL, the mass fraction of sodium hydroxide solution is 50%, and the molar ratio of amino groups on the modified zeolite, amino groups on the functionalized zinc organic framework and the modifier is 1:1:1.1.
[0074] The usage ratio of the composite matrix and acryloyl chloride described in step B3 is 1g:1.5mL, the usage of p-toluenesulfonamide is 0.2% of the mass of acryloyl chloride, the usage of the modified matrix, acrylamide, and methacryloyloxyethyltrimethylammonium chloride is 1g:40mmol:40mmol, and the usage of ammonium persulfate is 0.5% of the mass of acrylamide.
[0075] Comparative Example 1
[0076] Compared with Example 1, this comparative example uses bamboo fiber instead of modified fiber, and the other steps are the same.
[0077] Comparative Example 2
[0078] Compared with Example 1, no modified fiber was added in this comparative example, and the remaining steps were the same.
[0079] Comparative Example 3
[0080] Compared with Example 1, no modified filler was added in this comparative example, and the remaining steps were the same.
[0081] Comparative Example 4
[0082] Compared with Example 1, this comparative example uses zeolite instead of the modified filler, and the other steps are the same.
[0083] Comparative Example 5
[0084] Compared with Example 1, this comparative example did not add modified zeolite, and the remaining steps were the same.
[0085] The modified membranes prepared in Examples 1-3 and Comparative Examples 1-5 were used to filter NH 4 + The NH 4 + The removal rate of , the test results are shown in the following table.
[0086]
[0087] From the above table, we can see that this application has a good NH 4 + Remove effect.
[0088] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A wastewater deammoniation process based on ion exchange fibers, characterized in that: Specifically, the method comprises the following steps: putting wastewater into a liquid storage bottle, connecting a water pump, a liquid flow meter and the cavity side of a hollow fiber membrane contactor to form a circulation loop, the shell side of the hollow fiber membrane contactor is sequentially connected with a valve, a vacuum gauge and a vacuum pump, and the filter membrane in the hollow fiber membrane contactor is a modified filter membrane; The modified filter membrane is prepared by the following steps: Dissolving polyvinylidene fluoride in N,N-dimethylacetamide, adding lithium chloride monohydrate, modified fiber and modified filler and mixing evenly to obtain a casting solution, scraping the casting solution and soaking it in deionized water, taking it out and drying it to obtain a modified filter membrane; The modified fiber is prepared by the following steps: Step A1: After mixing and stirring bamboo fiber and sodium hydroxide solution, washing with deionized water until neutral to obtain activated fiber, and mixing and reacting the activated fiber, lithium chloride, maleic anhydride, 4-dimethylaminopyridine and N,N-dimethylacetamide to obtain pretreated fiber; Step A2: mixing the pretreated fiber, glycidyl methacrylate, benzoyl peroxide, deionized water and N,N-dimethylformamide for reaction, heating to continue the reaction, adding sodium aminosulfonate, and continuing the reaction to obtain a modified fiber; The modified filler is prepared by the following steps: Step B1: After mixing and stirring zeolite, calcium chloride hexahydrate and deionized water, vacuum drying is performed, the substrate is dispersed in ethanol, stirred and KH550 and deionized water are added to react to obtain a modified zeolite, and 2-aminoterephthalic acid, zinc nitrate hexahydrate and N,N-dimethylformamide are mixed and reacted to obtain a functionalized zinc organic framework; Step B2: Ethylene glycol, epichlorohydrin, tetrabutylammonium bromide and N,N-dimethylformamide are uniformly mixed, nitrogen is introduced for protection, a reaction is carried out, a sodium hydroxide solution is added, a reaction is carried out to obtain a modifier, and the modified zeolite, a functionalized zinc organic framework and N,N-dimethylformamide are mixed and stirred, and the modifier is added, and a reaction is carried out to obtain a composite matrix; Step B3: Disperse the composite matrix in tetrahydrofuran, stir and add acryloyl chloride and p-toluenesulfonamide to react to obtain a modified matrix, mix the modified matrix, acrylamide, methacryloyloxyethyltrimethylammonium chloride and deionized water evenly, introduce nitrogen protection, stir and add ammonium persulfate to react to obtain a modified filler.
2. A wastewater deammoniation process based on ion exchange fiber according to claim 1, characterized in that: The mass ratio of the bamboo fiber and the sodium hydroxide solution described in step A1 is 1:20, and the mass ratio of the activated fiber, lithium chloride and maleic anhydride is 1:1:
2.
3. The wastewater deammoniation process based on ion exchange fiber according to claim 1, characterized in that: The amount ratio of the pretreated fiber, glycidyl methacrylate and sodium aminosulfonate described in step A2 is 1 g:3 mL:0.5 g.
4. The wastewater deammoniation process based on ion exchange fiber according to claim 1, characterized in that: The dosage ratio of the zeolite, calcium chloride hexahydrate and deionized water in step B1 is 1 g:8 g:20 mL, the dosage of KH550 is 1.5% of the mass of the zeolite, and the molar ratio of 2-aminoterephthalic acid and zinc nitrate hexahydrate is 1:
4.
5. The wastewater deammoniation process based on ion exchange fiber according to claim 1, characterized in that: The amount ratio of ethylene glycol, epichlorohydrin, tetrabutylammonium bromide and sodium hydroxide solution in step B2 is 100mmol:200mmol:0.5g:30mL, and the molar ratio of the amino group on the modified zeolite, the amino group on the functionalized zinc organic framework and the modifier is 1:1:1.
1.
6. A wastewater deammoniation process based on ion exchange fiber according to claim 1, characterized in that: The usage ratio of the composite matrix and acryloyl chloride in step B3 is 1 g:1.5 mL, and the usage ratio of the modified matrix, acrylamide, and methacryloyloxyethyltrimethylammonium chloride is 1 g:40 mmol:40 mmol.
